Incorporating Stream Features into Groundwater Contouring Tools Within GIS. Issue 2 (21st March 2015) - Bannister, Roger; Kennelly, Patrick
Abstract: Hydrogeologists often are called upon to estimate surfaces from discrete, sparse data points. This estimation is often accomplished by manually drawing contours on maps using interpolation methods between points of known value while accounting for features known to influence the water table's surface. By contrast, geographic information systems (GIS) are good at creating smooth continuous surfaces from limited data points and allowing the user to represent the resulting surface resulting with contours, but these automated methods often fail to meet the expectations of many hydrogeologists because they do not include knowledge of other influences on the water table. In this study, we seek to fill this gap in the GIS‐based methodology for hydrogeologists through an interactive tool that shapes an interpolated surface based on additional knowledge of the water table inferred from gaining or losing streams. The modified surface is reflected in water table contours that, for example, "V" upstream for gaining streams, and can be interactively adjusted to fit the user's expectations. By modifying not only the contours but also the associated interpolated surface, additional contours will follow the same trend, and the modified surface can be used for other analyses like calculating average gradients and flow paths. The tool leverages Esri's ArcGIS Desktop software, building upon a robust suite of mapping tools. We see this as a prototype for other tools that could be developed for hydrogeologists to account for variations in the water table inferred from local topographic trends, pumping or injection wells, and other hydrogeologic features.